2017
DOI: 10.21837/pm.v15i4.314
|View full text |Cite
|
Sign up to set email alerts
|

What Drives House Price in Malaysia? In Search of an Alternative Pricing Benchmark for Islamic Home Financing

Abstract: The current practise of the Islamic banks to rely on market interest rate as pricing benchmark for their home financing products has been a subject of intense debate among many parties. Muslim scholars have warned that it is highly discouraged as it could lead to a possible convergence between the practices of the Islamic and conventional banks. This paper intends to address the financing issues in the discussion of human settlement or housing policy by presenting the determinants for house price index as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In this paper, the product refers to residential property. As a result of this technique, the index that was produced is able to include certain characteristics of the property, such as location, house type, neighborhood classification and much more (Kassim et al, 2017). It was also revealed that the base year shown in the index is intended to reflect the changes of residential property prices due to the preferences shown by the buyers and the emergence of new trends in the property market.…”
Section: 3malaysia House Price Indexmentioning
confidence: 99%
“…In this paper, the product refers to residential property. As a result of this technique, the index that was produced is able to include certain characteristics of the property, such as location, house type, neighborhood classification and much more (Kassim et al, 2017). It was also revealed that the base year shown in the index is intended to reflect the changes of residential property prices due to the preferences shown by the buyers and the emergence of new trends in the property market.…”
Section: 3malaysia House Price Indexmentioning
confidence: 99%
“…Housing price index is one of the widely used indicators in real estate property market as it portrayed the general fluctuation of housing prices across the period. On top of it, housing price index served as a broad indicator for the operation and transaction of the property markets (Kassim, Redzuan, & Harun, 2017;Xin, Burhan, & Diah, 2019). The index is based on the hedonic approach to price measurement using multivariate regression analysis with 1990 as the base year.…”
Section: Introductionmentioning
confidence: 99%